PEMBENTKAN KARAKTER KERJA KERAS PADA SISWA MELALUI KEGIATAN HIZBUL WATHAN (Studi Kasus di SMA Muhammadiyah 2 Sukoharjo) - Suryanto, Eko; Wiyono, W.; Setiyono, Agus (HISTORIKA, 2017)
This study aims to describe the character's hard work on the formation of students through the activities of the Hizbul Wathan (HW) at SMK Muhammadiyah 2 Sukoharjo. This type of research is a qualitative single case study with strategy. Data sources the study consisted of informants, places and events, as well as documents. Using data collection techniques interviews, observation, documentation, and Forum Group Discussion (FGD). The validity of the data using triangulation techniques, sources, and researchers. Data analysis using interactive models, Miles and Huberman.The results showed that the activities of the Hizbul Wathan in SMK Muhammadiyah 2 Sukoharjo was made for the formation of character means hard work on students. The formation of the character's hard work reflected in the skills that must be mastered students such as line-marching, playing, sports first aid kits, Trommel, spirituality, to the camp. Hard work character's was also established through the promise and law Wizard HW. The promise of Pandu pronounced voluntarily by members when appointed to be a member of the initial commitment is for committing yourself in settling and keeping our promises. While the legislation is a provision that moral Pandu made a habit of behaving yourself in and behave as citizens berakhlaq noble.Â